Lawlessness and Economics : Alternative Modes of Governance. - Dixit, Avinash K. (Princeton University Press, 2011)
How can property rights be protected and contracts be enforced in countries where the rule of law is ineffective or absent? How can firms from advanced market economies do business in such circumstances? In Lawlessness and Economics, Avinash Dixit examines the theory of private institutions that transcend or supplement weak economic governance from the state. In much of the world and through much of history, private mechanisms--such as long-term relationships, arbitration, social networks to disseminate information and norms to impose sanctions, and for-profit enforcement services--have grown.